Forgiveness in human-machine interaction - Holtzman, Inbal; Nimrod, Galit (Frontiers in Computer Science, 2025)
Forgiveness has been extensively studied across various academic fields, but not in relation to Human-Machine Interaction (HMI). The work presented in this article aims to answer two interrelated questions: what is forgiveness in HMI, and how do we forgive an erring technology? Relying on a literature review of both forgiveness and HMI studies, the article offers a holistic definition of the concept, according to which forgiveness in HMI is a shift in the users’ feelings, from negative to positive, that prevents the users from abandoning the erring technology and allows them to keep using it without resentment. Based on a pioneering focus groups study with a convenience sample of 27 young adults, four forgiveness mechanisms are illustrated: (1) evaluating the cost of the error against the benefits of using the technology; (2) transferring responsibility for technology errors to humans (either those “behind the technology” or the users); (3) communicating with or about the technology; and (4) accepting the technology’s faults. The results suggest that users undergo complex cognitive and emotional processes when faced with a technological error. As forgiveness is one of the most critical aspects of every relationship, the conceptualization and preliminary study presented here may serve as a starting point for a new area of research and as a springboard for an essential scholarly discussion.